PERAN ILMU LINGUISTIK DALAM PERKEMBANGAN TEKNOLOGI INFORMASI DAN SAINS: The Role of Linguistics in the Development of Information Technology and Science - I Gusti Ngurah Octova Seventilofa; Ngurah Artha Yoga Pratama; I Gusti Ngurah Bagus Yoga Widiadnya (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
The rapid development of information technology and science has increased the need for interdisciplinary collaboration, including the contribution of linguistics. Linguistic knowledge is no longer limited to the study of language but has become an essential foundation for developing various digital technologies, particularly those related to human-computer interaction and language processing. This study aims to examine the role of linguistics in supporting the advancement of information technology and science. The research employed a qualitative approach using a literature review method by analyzing relevant books, journal articles, and scientific publications. The collected data were analyzed descriptively to identify the contribution of linguistic concepts to technological innovation and scientific development. The findings reveal that linguistics plays a significant role in the development of Natural Language Processing (NLP), machine translation, speech recognition, virtual assistants, sentiment analysis, and other artificial intelligence applications. In addition, linguistics contributes to improving scientific communication by enhancing the clarity, accuracy, and effectiveness of knowledge dissemination across disciplines. The study concludes that linguistics has become an important interdisciplinary field that supports technological innovation and scientific progress, making collaboration between linguistics, information technology, and science increasingly necessary in the digital era